Homogeneous eigenvalue problems in Orlicz-Sobolev spaces - Bonder, Julián Fernández; Salort, Ariel; Vivas, Hernán (Topological Methods in Nonlinear Analysis, 2023)
In this article we consider a homogeneous eigenvalue problem ruled by the fractional g-Laplacian operator whose Euler-Lagrange equation is obtained by minimization of a quotient involving Luxemburg norms. We prove existence of an infinite sequence of variational eigenvalues and study its behavior as the fractional parameter s1 among other stability results.